The effect of ownership on the prudential behavior of banks – The case of China - Jia, Chunxin (Journal of Banking & Finance, 2009)
Although the relationship between bank ownership and performance is the current focus of much research, this paper investigates the relationship between ownership and the prudential behavior of banks. Using Chinese data, I show that lending by state-owned banks has been less prudent than lending by joint-equity banks, but has improved over time. This is consistent with the hypothesis that accountability to shareholders and depositors gives joint-equity banks a better incentive than state-owned banks to engage in prudent lending, and with the hypothesis that the reform of the banking system has improved the incentive for state-owned banks to behave more prudently in their lending.